2021
DOI: 10.1007/jhep12(2021)166
|View full text |Cite
|
Sign up to set email alerts
|

Conformally soft fermions

Abstract: Celestial diamonds encode the global conformal multiplets of the conformally soft sector, elucidating the role of soft theorems, symmetry generators and Goldstone modes. Upon adding supersymmetry they stack into a pyramid. Here we treat the soft charges associated to the fermionic layers that tie this structure together. This extends the analysis of conformally soft currents for photons and gravitons which have been shown to generate asymptotic symmetries in gauge theory and gravity to infinite-dimensional fer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…In [16] we established how to analytically continue the bulk conformal primary wavefunctions Φ ǫ ∆,J off the principal series to capture conformally soft modes and demonstrated that the operators defined via the inner-product dictionary O ǫ ∆,J = i( Ôs , (Φ −ǫ ∆,J ) * ) (1.6) correspond to the anticipated soft charges in each instance of a known asymptotic symmetry (large U(1), supertranslations, superrotations) in gauge theory and gravity (s = 1, 2) at the expected integer values of ∆. This was extended to the supergravity case in [17]. The operators O ∆,J indeed become the canonical charge for a corresponding asymptotic symmetry whenever the wavefunctions Φ ∆,J is pure gauge [16], which is the case for 1 − s < ∆ ≤ 1, and we refer to them as Goldstone wavefunctions.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In [16] we established how to analytically continue the bulk conformal primary wavefunctions Φ ǫ ∆,J off the principal series to capture conformally soft modes and demonstrated that the operators defined via the inner-product dictionary O ǫ ∆,J = i( Ôs , (Φ −ǫ ∆,J ) * ) (1.6) correspond to the anticipated soft charges in each instance of a known asymptotic symmetry (large U(1), supertranslations, superrotations) in gauge theory and gravity (s = 1, 2) at the expected integer values of ∆. This was extended to the supergravity case in [17]. The operators O ∆,J indeed become the canonical charge for a corresponding asymptotic symmetry whenever the wavefunctions Φ ∆,J is pure gauge [16], which is the case for 1 − s < ∆ ≤ 1, and we refer to them as Goldstone wavefunctions.…”
Section: Introductionmentioning
confidence: 93%
“…The inner product (2.22) serves to project out the polarization tensors, so that the operator O − ℓ (ω, w, w) is just the annihilation operator a ℓ (ω, w, w). This is particularly useful for the half-integer spin case [17]. We can then use the transforms (2.1) and (2.3) to go to the other bases.…”
Section: The Extrapolate Dictionarymentioning
confidence: 99%
See 1 more Smart Citation
“…In [8], the supersymmetric w 1+∞ algebra has been identified with the corresponding soft current algebra in the supersymmetric Einstein-Yang-Mills theory. The relevant works on the celestial holography in the various directions can be found in [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. See [1] for more complete literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a new understanding of the gravitational renormalization procedure connecting finite to asymptotic surfaces has been achieved [17,19,53,64]. On the celestial side, some of the highlights include the reformulation of scattering amplitudes into a basis of asymptotic boost eigenstates [23,24,[65][66][67], an ever-growing catalogue of celestial symmetries [31,33,[68][69][70][71][72][73][74][75][76][77] and their associated constraints [32,[34][35][36]78], as well as a framework amenable to the use of standard conformal field theory (CFT) methods [79][80][81][82][83] for gravity in AFS. Intriguingly, a w 1+∞ structure [84][85][86] was recently encountered in the algebra of the infinite tower of conformally soft graviton symmetries [37,38].…”
mentioning
confidence: 99%